2020
DOI: 10.1109/tdei.2020.008432
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric coupling in PVDF/Nano NaNbO3/NanoNi composites: Influence of Ni particles aspect ratio

Abstract: In this work, three phase magnetoelectric nanocomposites are successfully prepared by solvent casting from α-PVDF. The extrinsic piezoelectric effect is insured by 20 vol% of NaNbO 3 ferroelectric nanoparticles prepared by the hydrothermal process. Nickel is chosen as the magnetic phase. In order to maintain insulation, electrical percolation is avoided by using nickel contents lower than the percolation threshold. Two different morphologies are employed: spherical nanoparticles (NiNPs) and nanochains (NNCs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Moreover, these materials offer unique advantages, such as they can be fabricated into different shapes, on molded structures and curved surfaces, thus, making them suitable for applications such as sensors, transducers, actuators, data storage, spintronics, and miniature antennas [5][6][7][8][9][10]. Magnetoelectric coupling in such polymers can be formed with the incorporation of ferromagnetic nanoparticles, and the coupling properties can be tuned by varying content and shape of nanoparticles in the composite systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these materials offer unique advantages, such as they can be fabricated into different shapes, on molded structures and curved surfaces, thus, making them suitable for applications such as sensors, transducers, actuators, data storage, spintronics, and miniature antennas [5][6][7][8][9][10]. Magnetoelectric coupling in such polymers can be formed with the incorporation of ferromagnetic nanoparticles, and the coupling properties can be tuned by varying content and shape of nanoparticles in the composite systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many attempts have been made to produce magnetoelectric coupling between ferroelectric PVDF and ferromagnetic nanoparticles with good dispersion of nanoparticles [12,21]. However, little attention has been dedicated to developing the magneto-electric coupling in the copolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many applications such as magnetic field sensing, high anisotropy is desirable to tailor the sensor signal-to-noise ratio and directionality. To date, shaping particles into high aspect ratios has been shown to improve the magnetostriction efficiency of magnetoelastic composites, 33 with some recent research exploiting this in nano-wire, 34 nano-ellipsoid, 35 and nano-chain 36 particles produced by using bottom-up processing routes. Further, chaining of low-aspect ratio particles has also been reported using magnetic fields during the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also reported a magnetoelectric coupling with nickel particles in P(VDF-TrFE) [17] and in three-phased magnetoelectric composites. [18,19] In comparison with ferrites, nickel exhibits higher remnant magnetization at ambient temperature, which can be interesting to improve the magnetoelectric coupling in the composites. The main drawback of using metal instead of ceramics is the increase of the conductivity; it makes the poling of the matrix harder and then decreases the piezoelectric coefficient (d 33 ), especially for P(VDF-TrFE), which displays a high poling field 70 MV m À1 .…”
Section: Introductionmentioning
confidence: 99%